Chatbot-Based Solo Culinary Tourism Management Information System Web - Setyawati, Monica; Nugroho, Agus Cahyo; Harnadi, Bernardius (Journal of Business and Technology, 2024)
Solo city is an ancient Indonesian city home to various cultural artifacts from ancient to modern eras. Finding famous Solo culinary treats on Google can be difficult for many individuals inside and outside of Solo. This study was conducted to make it simple for people living in and outside of Solo to find delicious foods in Solo by improving the Solo culinary website. Users can access the Solo Culinary tour SIM web by supplying details about culinary locations, addresses, and Solo Culinary phone numbers. Try the Solo chatbot and WhatsApp bot on the Solo culinary tourism SIM site to see their effect on implementing the Solo chatbot and Solo culinary tourism. PHP, HTML, and CSS were used to construct the Making Solo food website. A chatbot-based Solo culinary tour SIM online and system testing approach employing interviews was used in this project. For the author's data analysis and to make it easier for locals inside and outside of Solo to enjoy the culinary delights of Solo, interviews were held in the city. The study's findings demonstrate that residents within and outside of Solo can discover culinary information, locations, and phone numbers for Solo Culinary by using the chatbot.